1978
DOI: 10.1901/jaba.1978.11-11
|View full text |Cite
|
Sign up to set email alerts
|

POLICE EVALUATION RESEARCH: AN EXPERIMENTAL AND COST‐BENEFIT ANALYSIS OF A HELICOPTER PATROL IN A HIGH CRIME AREA1

Abstract: The significance of a helicopter patrol procedure directed toward prevention of home burglaries was evaluated from experimental and cost-benefit perspectives. The helicopter patrolled one city zone from 9 a.m. to 5 p.m. for two 12-day periods. Each 12-day period was separated by a baseline period in which only normal patrol-car levels were maintained. Significantly reduced burglary levels during the intervention periods, compared to baseline periods, documented the experimental significance of the helicopter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 4 publications
1
16
0
1
Order By: Relevance
“…It is unfortunate that the series of experiments by Schnelle and his colleagues (Schnelle et al, 1975(Schnelle et al, , 1977(Schnelle et al, , 1978(Schnelle et al, , 1979 all involved essentially within-subjects/ base-line designs rather than control groups. It is unfortunate that the series of experiments by Schnelle and his colleagues (Schnelle et al, 1975(Schnelle et al, , 1977(Schnelle et al, , 1978(Schnelle et al, , 1979 all involved essentially within-subjects/ base-line designs rather than control groups.…”
Section: Experiments On Larger Unitsmentioning
confidence: 99%
“…It is unfortunate that the series of experiments by Schnelle and his colleagues (Schnelle et al, 1975(Schnelle et al, , 1977(Schnelle et al, , 1978(Schnelle et al, , 1979 all involved essentially within-subjects/ base-line designs rather than control groups. It is unfortunate that the series of experiments by Schnelle and his colleagues (Schnelle et al, 1975(Schnelle et al, , 1977(Schnelle et al, , 1978(Schnelle et al, , 1979 all involved essentially within-subjects/ base-line designs rather than control groups.…”
Section: Experiments On Larger Unitsmentioning
confidence: 99%
“…The results showed reductions in crime during the night but not during daylight patrols although the authors noted that projected costs would be prohibitive if full scale implementation was achieved. A follow-up study found that helicopter patrols reduced burglaries compared to periods when helicopter patrols were not in effect (Schnelle et al, 1978) with benefit=cost ratios favoring helicopter patrols. A subsequent study showed decreases in residential burglaries in high-density areas but not low-density areas when police patrols were in effect.…”
Section: Crime and Delinquencymentioning
confidence: 99%
“…Schnelle et al (1978) reported data showing the cost efficiency of helicopter patrol in reducing home burglaries within some specific areas of Nashville.…”
mentioning
confidence: 99%
“…a technique called field interrogation, there were some mild reductions in malicious mischief and burglary incidents. Schnelle et al (1978) reported data showing the cost efficiency of helicopter patrol in reducing home burglaries within some specific areas of Nashville.…”
mentioning
confidence: 99%